Properties of Cellulose Fibres and Waste Plastic Modified Porous Friction Course Mixes - Subbarao Nagabhushanarao Suresha; George Varghese; Ayyalasomayajula Udya Ravi Shankar (The Baltic Journal of Road and Bridge Engineering)
This paper summarises the laboratory investigation on porous friction course mixes that were modified with cellulose fibres and waste plastics. Porous friction course mixes of three diff erent aggregate gradations were tested for predetermined binder content. The influence of each modifier on the volumetric properties, permeability, aged abrasion loss, and moisture susceptibility of porous friction course mixes were evaluated. In order to determine the significance level of effect of modifiers on the above properties, the tests for analysis of variance (ANOVA) and Tukey’s multiple mean comparisons were performed. Results of statistical analyses indicate that the gradations are major source of variations in all response properties. However, modifiers too appreciably contributed in reducing the moisture-induced damages. The findings suggest that shredded waste plastics are potentially useful as modifiers to porous friction course mixes.